PENERAPAN METODE PICTURE AND PICTURE DALAM PEMBELAJARAN CERITA FANTASI - Yunyun Yuna Amalia; Eli Syarifah Aeni (IKIP Siliwangi, 2019)
This research is motivated by the low value in writing fantasy stories on Madrasah Tsanawiyah students, this is proven by the results of observations with Indonesian teachers who say that students are less interested in learning to write fantasy stories because they are considered boring, so students lack learning and get grades less. Based on this, the formulation of the problem of this research is how the results before and after learning write fantasy stories using the method of picture and picture in class VII students. The purpose of this research is to find out the results before and after using the picture and picture method. The method used is an experimental one-group pretest-posttest design. The results showed that there were good and increasing differences between before and after using the picture and picture method. Based on the data obtained there are known differences from the test before using the method and the final test with the initial test average of 64.02 and the final test of 80.08 with a difference of 16.06. Judging from the increased student results it can be concluded that the use of the picture and picture method is suitable for use in learning to write fantasy stories.